A daily diary investigation of cannabis use and its diet and exercise correlates - Gibson, Laurel P.; Skrzynski, Carillon J.; Giordano, Gregory R.; Bryan, Angela D. (Frontiers in Psychology, 2023)
Background The increasing availability of legal-market cannabis products has raised many questions about potential harms and benefits of increased use. In particular, concerns have been raised about the possible negative impact of cannabis use on behavioral determinants of obesity and chronic disease, including diet and exercise. However, previous research is mixed and has largely relied on cross-sectional survey data and coarse measurements of cannabis use, underscoring the need for more rigorous research designs. Purpose The present study utilized longitudinal daily diary data to assess whether exercise and diet patterns differed between cannabis users and non-users and, within cannabis users, whether legal-market cannabis use, diet, and exercise covaried within individuals across time and based on cannabinoid content. Methods A sample of 98 participants (77 cannabis users, 21 non-users) completed a baseline appointment and a 30-day daily diary study assessing their daily cannabis use, diet, and exercise. Cannabis users were quasi-randomly assigned to use either a THC-dominant flower product (n = 36) or a CBD-containing flower product (n = 41) ad libitum over the course of the daily diary study. Participants were between the ages of 21 and 41 (M = 29.28) and were majority male (61.2%). Results At baseline, there were no differences in BMI or exercise behavior between users and non-users. Likelihood of exercising and exercise minutes per day over the 30-day period also did not differ between users and non-users, nor did these outcomes differ on cannabis use vs. non-use days among cannabis using participants. In contrast, there was some evidence for a relationship between cannabis use and dietary measures. At baseline, non-users scored higher on the Healthy Eating Index than users. Daily data also indicated that users consumed marginally more salty snacks and fast food per day relative to non-users, and users consumed more fruits/vegetables and marginally more salty snacks on cannabis use days vs. non-use days. Interestingly, among users, no associations were dependent on the cannabinoid content of their assigned product. Conclusion Findings suggest little association between cannabis use and exercise but underscore the need for further research on how cannabis use may impact dietary patterns. Future research should examine the impact of cannabis on non-behavioral pathways to obesity and chronic disease (e.g., metabolism).